A UV resonance line echo from a shell around a hydrogen-poor superluminous supernova. (November 2018) - Lunnan, R.; Fransson, C.; Vreeswijk, P.; Woosley, S.; Leloudas, G.; Perley, D.; Quimby, R.; Yan, Lin; Blagorodnova, N.; Bue, B.; Cenko, S.; De Cia, A.; et al.
Abstract Hydrogen-poor superluminous supernovae (SLSN-I) are a class of rare and energetic explosions that have been discovered in untargeted transient surveys in the past decade1, 2 . The progenitor stars and the physical mechanism behind their large radiated energies (about 1051 erg or 1044 J) are both debated, with one class of models primarily requiring a large rotational energy3, 4 and the other requiring very massive progenitors that either convert kinetic energy into radiation through interaction with circumstellar material (CSM)5–8 or engender an explosion caused by pair-instability (loss of photon pressure due to particle–antiparticle production)9, 10 . Observing the structure of the CSM around SLSN-I offers a powerful test of some scenarios, although direct observations are scarce11, 12 . Here, we present a series of spectroscopic observations of the SLSN-I iPTF16eh, which reveal both absorption and time- and frequency-variable emission in the Mgii resonance doublet. We show that these observations are naturally explained as a resonance scattering light echo from a circumstellar shell. Modelling the evolution of the emission, we infer a shell radius of 0.1 pc and velocity of 3, 300 km s−1, implying that the shell was ejected three decades before the supernova explosion. These properties match theoretical predictions of shell ejections occurring because of pulsational pair-instability and imply that the progenitor had a helium core mass of about 50–55M ⊙, corresponding to an initial mass of about 115M ⊙ . Probing the pre-explosion environments of hydrogen-poor superluminous supernovae is important for understanding how they exploded. Here, Lunnan et al. infer the presence of a fast-moving circumstellar shell around iPTF16eh through the detection of a resonance-line light echo, which indicates the massive progenitor experienced pulsational pair instability shell ejections.